Fortifikasi mie kering dengan tepung sorgum sebagai makanan fungsional sumber serat pangan - Almadany, Muhyiddin Ibnul Arabi; Hidayanti, Lilik; Susilowati, Prima Endang (Program Studi Gizi, 2024)
The teenage age group is vulnerable to obesity problems. The consumption pattern of foods high in fat and low in fiber is starting to increase, especially fast food, so that the need for balanced nutrition cannot be met. Instant noodles are a food that is often chosen because they are easy and quick to cook. Providing fortification in noodles is an alternative for reducing obesity rates. Sorghum is a source of high fiber from local food which can be used as an ingredient in making noodles. The addition of sorghum flour in making dry noodles is carried out as an effort to increase the nutritional value of food, especially dietary fiber and to utilize local food which is still underused in some areas. This research aims to examine the acceptability and dietary fiber content of dry noodles with the addition of sorghum flour. The design of this research is experimental. The design in this study used a factorial Completely Randomized Design (CRD) with a ratio of wheat flour to sorghum flour of 100:0 (F0), 90:10 (F1), 80:20 (F2), and 70:30 (F3). The analysis used for organoleptic data was Kruskal-wallis with the Mann-Whitney test. Food fiber content was tested using the enzymatic gravimetric method. The results of the research show that the acceptability results based on organoleptics which include color, aroma, texture and taste of dry sorghum flour noodles show significant differences in taste, texture and color, but not significant differences in aroma. The best treatment for sorghum flour dry noodles based on acceptability is F1 which is a 10% sorghum flour formula with a dietary fiber content of 7.24% and can be said to be a functional food source of dietary fiber.